Influence of roasting conditions on physicochemical and fatty acid profile of raw and roasted cashew kernel (Anacardium occidentale) grown in Nigeria - Olatidoye, Olawale Paul (Array, 2020)
This study aimed at evaluating the effect of roasting conditions on some physicochemical and nutritional properties of cashew nut lipid fractions at different temperature (100–160ᵒC) and time (20–60 min). Raw and roasted cashew nuts were also analyzed for their composition in fatty acid by GC-FID. Physicochemical properties of the oil showed that the oil yield of roasted cashew nut oil (56.67-31.67%) was significantly higher compared to unroasted oil (47.43%). Also, cashew nut oil with mean values revealed that acid (12-0.86 mg KOH/g of oil); saponification value (138.10-169.06 mgKOH/g of oil), iodine value (55.50-36.19 mg of I/100g of oil); TBA(0.012-0.18mg); p-anisidine value (0.55-0.66); peroxide value (7.26-3.05 meq/kg) and free fatty acid (1.07-1.50 % oleic acid) which indicated that cashew nut oil is edible, non-drying and may not be suitable for soap making. Results of GC-FID analysis of the ethyl esters of saturated and unsaturated fatty acid of raw and roasted cashew nut showed that unsaturated fatty acids represented 60.57% for unroasted samples with roasted samples (79.67–83.67%) while saturated fatty acids recorded (16.11–37.65%). The fatty acid composition of the oils shows the presence of four main fatty acids: palmitic (9.25–29.50%); stearic (4.4–9.34%); oleic (34.75–65.60%); and linoleic (1.35–20.66%) with high oleic to linoleic ratio associated with high oil stability. The order of increase is oleic >linoleic >palmitic >stearic in all the samples irrespective of roasting conditions. The result showed that minor changes occur in the fatty acids composition as the roasting temperature and time increased. It was concluded that the heat treatment used does not significantly affect the fatty acid profile content of cashew nuts preserving its antioxidant activity along with other bioactive compounds contained therein.